PENGARUH ORGANIZATION LEARNING TERHADAP COMPETITIVE POSITIONING MELALUI ACCOUNTING INFORMATION SYSTEM TERHADAP PERUSAHAAN MANUFAKTUR - Angelina Zipora (Business Accounting Review, 2015)
This study was conducted to examine the relationship intervening of Accounting Information System. The sample in this study were 60 respondents who plays as managers. This study used a qualitative approach. The data for this study were obtained through questionnaires and the results of this study showed that there was a positive affect on the organization learning to the competitive positioning in the company, positive influence of organization learning to accounting information system, and the positive effect of accounting information system to competitive positioning but not significant